# Match the following

For (a) a × 1 = a

So, we can match (a) with (vi).

For (b) 1 = Multiplicative identity

1 is multiplicative identity because any integer multiplied with 1 gives the same integer.

So, we can match (b) with (iii).

For (c) (-a) ÷ (-b) = a ÷ b

As

…(i)

And …(ii)

Comparing equations (i) and (ii), we get

(-a) ÷ (-b) = a ÷ b

So, we can match (c) with (v).

For (d) a × (-1) = -a

As a × (-1) = -a × 1 = -a

So, we can match (d) with (vii).

For (e) a × 0 = 0

0 multiplied with any integer equals to 0.

So, we can match (e) with (viii).

For (f) (-a) ÷ b = a ÷ (-b)

As …(i)

And

…(ii)

Comparing equations (i) and (ii), we get

(-a) ÷ b = a ÷ (-b)

So, we can match (f) with (iv).

For (g) 0 = additive identity

0 is additive identity because any integer added to 0 gives the same integer.

So, we can match (g) with (ii).

For (h) a ÷ (-a) = -1

As

a ÷ (-a) = -1

So, we can match (h) with (ix).

For (I) -a = Additive inverse of a

(-a) is additive inverse because integer a added with –a gives 0.

So, we can match (I) with (i).

Arranging it into table:

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.